NEW WAVE OF CHINESE ARCHITECTURE AND CONSTRUCTION. REVIEW OF THE CPR MOST OUTSTANDING BUILDINGS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The most outstanding buildings of the Chinese People’s Republic for the last decade areobserved. The contemporary projecting and construction techniques with the use of steel structures are analyzed for large-scale projects. Keywords:Chinese building megaprojects, construction, large-span steel structures